2021
DOI: 10.18231/j.ijceo.2021.012
|View full text |Cite
|
Sign up to set email alerts
|

The attitude towards strabismus and barriers for its treatment in parents from rural and urban areas

Abstract: It has been observed that children having strabismus who are being left untreated face a lot of psychosocial and functional difficulties in adulthood. In this study, an attitude and a barrier scale was structured and validated on the basis of the adult strabismus 20 questionnaire and a Barrier Scale. The attitude scale had two subscales-psychosocial subscale and functional subscale. A total of 1747 children; 828 from urban and 919 from rural areas, between the age group of 5 to 12 years were screened from urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…We found 739 records with quantitative information on horizontal strabismus, 427 were population-based, and 312 were clinic-based ( Figure 1 ). Among the 427 population-based studies that reported on the prevalence of horizontal strabismus, 74 (17.33%) disclosed the distribution by gender in cohorts and in cases [ 10 , 14 - 16 , 22 , 25 , 32 - 98 ]. One of these studies was removed because it exclusively examined people above the age of 50 years [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We found 739 records with quantitative information on horizontal strabismus, 427 were population-based, and 312 were clinic-based ( Figure 1 ). Among the 427 population-based studies that reported on the prevalence of horizontal strabismus, 74 (17.33%) disclosed the distribution by gender in cohorts and in cases [ 10 , 14 - 16 , 22 , 25 , 32 - 98 ]. One of these studies was removed because it exclusively examined people above the age of 50 years [ 63 ].…”
Section: Resultsmentioning
confidence: 99%
“…Are parents more worried about strabismus in their daughters than in their sons? Indeed, several studies indicate that parents are more concerned about the looks of their daughters than their sons [ 11 , 23 , 25 ]. Since strabismus is mostly diagnosed and treated in childhood, this points to the parents as the decision makers and to the contribution of the parents as a source of the gender bias.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that some parents, specifically the less educated ones, showed a lack of understanding of strabismus, leading to a late diagnosis and ineffective countermeasures toward the disease. Contradicting these reports, a study carried out among Indian parents in urban areas [ 13 ] found that many of the parents (53.3%) were not concerned about what people think about their children's eyes, and nearly half of them (47.7%) never thought that people noticed their child's eyes unless they said something about it.…”
Section: Discussionmentioning
confidence: 99%